Prospects for the Formation of a Smart Destination as a Determining Factor in the Modernization of Urban Infrastructure and a Means of Sustainable Urban Tourism Development in Kazakhstan - BERDIBEKOVA, Amina; SADYKOVA, Guldana; ALPEISSOVA, Sholpan; PARIMBEKOVA, Lyazzat; ZHANABAYEVA, Zhanar (Journal of Environmental Management and Tourism, 2022)
New requirements of society for the provision of tourist services are shaped by informatization and the transformation of society into one of modern technology. The value of the innovative component of tourist service provision, modernization of priorities in the consumer market, communicative interaction with consumers using the latest technology, and other components call for new approaches and methods in the formation of the complex of relationships in tourist destinations. In this, of importance is the need for scientific research into the formation of a smart destination of the megapolis as a certain factor in the modernization of urban infrastructure. The purpose of the study is to discover prospects for the formation of a smart tourist destination of the metropolis as a decisive factor in the modernization of urban infrastructure and the means of sustainable development of urban tourism. Analysis of research results points to the key technological developments used in smart tourist destinations, as well as the universal mobile travel applications most relevant in Kazakhstan's megacities. The authors conclude that smart tourist destinations can function as the components (elements) of smart cities, giving opportunities for the formation and promotion of the tourist product and the development of urban infrastructure.